OBSCURITY EFFECT: A VALUATION MATCH BETWEEN BUYER AND SELLER OF TIME-SENSITIVE AND VALUE-DEPRECIATING GOOD FOR THE SINGAPORE MILLENNIAL CONSUMER MARKET - Koh, Daniel (Digital Repository of Theses, 2023)
Behavioral economics is a study of decision-making from the perspective of individual’s or institutions’ behavior arising from a departure from the classical economic theory. One example would be the differences in setting buying price and selling price for the same product due to the attachment one has with it. In an uncertain environment where events change rapidly, consumers are not able to indicate their buying price and selling price of the same product rationally, leading to a disparity in prices. And this disparity can be noticeably huge. Over the past 50 years, researchers in the field of psychology, decision science, and economics have studied the varied nature of the irrationality of consumers,and concluded that loss aversion remains the most credible explanation for the disparity. While buyers seek market valuation of products, sellers seek compensation for losing a product when it is sold. Researchers have named this phenomenon the endowment effect. In our research, we have shown that the endowment effect does not apply to a particular class of products - the time-sensitive and value-depreciating products or TSVD products. The selling price is determined by the loss in losing the chance to sell the TSVD products across different points in time, which is fundamentally expressed in the Loss Aversion Sensitivity function or LAS function. And we have shown that the selling price on average can be higher than the buying price on average when consumers’ field of decision-making is obscured. We call this effect the obscurity effect. We researched the obscurity effect using a quantitative survey questionnaire and tested 6 hypotheses in within-subject and between-subject designs using non-parametric and parametric statistical methods. We concluded that the TSVD products follow the LAS function, and the behavioral pattern was disrupted when the obscurity effect is observed. In our discussion, we have provided some explanations for the obscurity effect. These explanations include concepts coming from cognitive psychology, social psychology, and emotions. Finally, we presented two use cases whereby businesses can benefit from curtailing the obscurity effect. Definitions used in this paper are defined by mathematical logic and reasoning.